Rethinking the occurrence of volunteering from the capability - opportunity - motivation perspective - Yijing, Huang (2026)
The COM-B model, proposed by Michie and colleagues, posits that capability (C), opportunity (O), and motivation (M) interact to generate behavior (B), offering a comprehensive framework for analyzing the conditions under which behavior occurs. While the COM-B model has been predominantly applied to health behavior interventions, we propose that it holds considerable potential for extension to positive behaviors such as volunteering. We introduce the COM-B framework to reconceptualize the occurrence of volunteering behavior, using university student volunteering as an illustrative case. We delineate the specific meanings of Capability, Opportunity, and Motivation within the volunteering context and explore conditions that enable volunteering as a behavior to occur. Regarding the Capability component, we distinguish between physical and psychological capability, emphasizing the central role of the latter for university student volunteering; Regarding opportunity, we differentiate physical opportunity from social opportunity and underscore the importance of perceived opportunity availability; Regarding the Motivation component, we integrate reflective and automatic motivation, proposing “wanting” as the critical mechanism that bridges the intention-behavior gap. We aim to provide a more comprehensive analysis of the conditions that generate volunteering behavior from the perspective of Capability, Opportunity and Motivation.